SOCIO-ECONOMIC DEVELOPMENT OF XINJIANG WITHIN THE FRAMEWORK OF THE WESTERN DEVELOPMENT STRATEGY OF CHINA - Д.А., Мaдиев; Ц., Чжaо (Journal of Oriental Studies, 2019)
This article discusses the process of socio-economic development of the Xinjiang Uygur Autono- mous Region since the formation of the People’s Republic of China. The Xinjiang Development Program, conducted within the framework of the PRC Government’s Strategic Plan for the Development of the West, shows the growing strategic importance of the region in promoting new international relations and ensuring the economic growth of this region. The socio-economic changes achieved in such areas as welfare of the population, construction of social facilities and implementation of infrastructure projects, heavy and light industry are reviewed and analyzed separately. Key words: China, Xinjiang Uygur Autonomous Region (XUAR), “Western Development”, economic development, infrastructure.